Network analysis of anxiety and depression in the functionally impaired elderly - Yang, Tianqi; Guo, Zhihua; Cao, Xiaoqin; Zhu, Xia; Zhou, Qin; Li, Xinhong; Wang, Hui; Wang, Xiuchao; Wu, Lin; Wu, Shengjun; Liu, Xufeng (Frontiers in Public Health, 2022)
Background Evidence from previous studies has confirmed that functionally impaired elderly individuals are susceptible to comorbid anxiety and depression. Network theory holds that the comorbidity emerges from interactions between anxiety and depression symptoms. This study aimed to investigate the fine-grained relationships among anxiety and depression symptoms in the functionally impaired elderly and identify central and bridge symptoms to provide potential targets for intervention of these two comorbid disorders. Methods A total of 325 functionally impaired elderly individuals from five communities in Xi'an, China, were recruited for our investigation. The GAD-7 and PHQ-9 were used to measure anxiety and depression, respectively. SPSS 22.0 software was used for descriptive statistics, and R 4.1.1 software was used for network model construction, expected influence (EI) evaluation and bridge expected influence (BEI) evaluation. Results In the network, there were 35 edges (indicating partial correlations between symptoms) across the communities of anxiety and depression, among which the strongest edge was A1 “Nervousness or anxiety”-D2 “Depressed or sad mood.” A2 “Uncontrollable worry” and D2 “Depressed or sad mood” had the highest EI values in the network, while A6 “Irritable” and D7 “Concentration difficulties” had the highest BEI values of their respective community. In the flow network, the strongest direct edge of D9 “Thoughts of death” was with D6 “Feeling of worthlessness.” Conclusion Complex fine-grained relationships exist between anxiety and depression in functionally impaired elderly individuals. “Uncontrollable worry,” “depressed or sad mood,” “irritable” and “concentration difficulties” are identified as the potential targets for intervention of anxiety and depression. Our study emphasizes the necessity of suicide prevention for functionally impaired elderly individuals, and the symptom “feeling of worthlessness” can be used as an effective target.